Determination of binding capacity and affinity constants of Sevelamer Hydrochloride and its market preparation - Biswas, Sushanta; Sultan, Md Zakir; Sajeeb, BK; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Sevelamer is an orally administered weakly basic anion exchange resin which consists of crosslinked polymeric amine that binds dietary phosphate in the gastrointestinal tract. This is approved for the treatment of hyperphosphatemia in adult patients with end-stage renal disease. The binding parameter constants of nonabsorbable sevelamer in its hydrochloride form were determined using the Langmuir approximation for its active pharmaceutical ingredient and 400 mg generic tablet dosage form (Sevel) at pH 4.0, 5.5 and 7.0. The binding parameters were also compared with the innovator product Renagel 400 mg tablet. The results demonstrate the equivalency of the dosage form at each pH in terms of the in vitro binding parameters. The results also demonstrate a shift in the binding mechanism from pH 4.0 to 7.0. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21858 Dhaka Univ. J. Pharm. Sci. 13(1): 37-49, 2014 (June)